Seventy years after Hiroshima and Nagasaki: Reflections on the consequences of nuclear detonation. (6th August 2015) - Unknown
Abstract : In this interview, conducted after their visit to Hiroshima, President Peter Maurer and President Tadateru Konoe reflect on the human cost of nuclear weapons and present the perspective of the International Red Cross and Red Crescent Movement on the Conferences on the Humanitarian Impact of Nuclear Weapons in Oslo, Nayarit, Mexico and Vienna, and the challenges ahead for nuclear disarmament.